Electromagnetic Simulation of Metamaterial Lens Antenna with Negative Refractive Index at 28GHz - Al Ghifarry, Mohamed Farouk; Kamardin, Kamilia; Yoshihide Yamada; Idris, Izni Husna (International Journal of Integrated Engineering, 2025)
Lens antennas are widely used to achieve multi-beam radiation patterns. When designed with negative refractive index (NRI) materials, these patterns improve further due to reduced lens thickness. Evaluating radiation characteristics requires electromagnetic simulation tools, but only a few can accurately model NRI properties. This paper explores the feasibility of using HFSS for such simulations. The study outlines the modeling approach, parameter settings, and computational techniques. Key results, including near-field, aperture amplitude and phase, and radiation patterns, are analyzed. To ensure accuracy, the simulated outcomes are compared with theoretical calculation.